Coronary Computed Tomography Angiography‐Based Tricuspid Annular Plane Systolic Excursion: Correlation with 2D Echocardiography. Issue 6 (24th January 2014) - Singh, Jaspreet; Borgstrom, Mark; Abidov, Aiden
<x xml:space="preserve">Abstract</x> Background Right heart evaluation on coronary computed tomography angiography (CCTA) is underutilized due to nonopacification of the right heart chambers and poor endocardial resolution. We analyzed feasibility and reproducibility of right heart functional analysis by measuring CCTA‐based tricuspid annular plane systolic excursion (CT‐TAPSE) on ECG‐gated CCTA and correlated the results with 2D transthoracic echocardiography (TTE)‐derived TAPSE (Echo‐TAPSE). Methods CT‐TAPSE was measured on a total population of 41 patients who had CCTA and TTE performed within 6 months of each other. Two independent CCTA readers performed analysis on reformatted four‐chamber view. Intra‐ and inter‐observer variability analysis was performed on 16 randomly selected patients. Correlative (Spearman's R) and Bland–Altman analysis was used to assess the level of agreement between the 2 methods and to compare CT‐TAPSE with Echo‐TAPSE. Results CT‐TAPSE measured by Readers 1 and 2 on 16 randomly selected patients, demonstrated excellent intra‐observer and inter‐observer agreement, with very close correlation (R > 0.80 and 2‐tailed P‐value of <0.001). When tested in the entire study population of 41 patients, CT‐TAPSE correlated closely with Echo‐TAPSE (R = 0.738, P < 0.001). Bland–Altman analysis indicated that the 2 methods provided similar measures as majority of values lay within the 95% confidence limits. Based on abnormal Echo‐TAPSE cutoff value of <16 mm, CT‐TAPSE identified impaired right ventricle (RV) function with sensitivity of 82% and specificity of 93%, respectively. Conclusion We demonstrated feasibility and reproducibility of assessing TAPSE on coronary CTA. RV functional analysis utilizing CT‐TAPSE is simple and reproducible methodology, and is in close agreement with Echo‐TAPSE.